PERAN KEHARMONISAN KELUARGA DAN PENERIMAAN TEMAN SEBAYA TERHADAP KONSEP DIRI REMAJA SMP DI DENPASAR (Jurnal Psikologi Udayana, 2015)
The self-concept is a very important mental aspect in a early adolescent’s life because it can influence their behavior. Self-concept is not innate, but rather influenced by environmental stimuli at an early age. Family condition is one of the environmental stimuli that can influence self-concept. In outside-the home life, the responses of peers while interacting also contribute significantly to the self-concept. This study aims to determine the roles of family harmony and peer acceptance to teenagers’ self-concept of Junior High School adolescent in Denpasar.Subjects in this study were 224 of Junior High School adolescent in Denpasar, represented by the State Junior High School 1 of Denpasar. Instruments in this study were self-concept scale, family harmony and scale of peer acceptance.The results of multiple regression analysis shows that R = 0.560 (F = 50.395, p